Precalculus: Mathematics for Calculus, 7th Edition

Published by Brooks Cole
ISBN 10: 1305071751
ISBN 13: 978-1-30507-175-9

Chapter 1 - Section 1.6 - Complex Numbers - 1.6 Exercises - Page 64: 68



Work Step by Step

$x^{2}-3x+3=0$ Use the quadratic formula to solve this equation. The formula is $x=\dfrac{-b\pm\sqrt{b^{2}-4ac}}{2a}$. For this equation, $a=1$, $b=-3$ and $c=3$. Substitute the known values in the formula: $x=\dfrac{-(-3)\pm\sqrt{(-3)^{2}-4(1)(3)}}{2(1)}=\dfrac{3\pm\sqrt{9-12}}{2}=...$ $...=\dfrac{3\pm\sqrt{-3}}{2}=\dfrac{3\pm\sqrt{3}i}{2}=\dfrac{3}{2}\pm\dfrac{\sqrt{3}}{2}i$ The answer is $x=\dfrac{3}{2}\pm\dfrac{\sqrt{3}}{2}i$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.